Synthesis, X-Ray Structure Characterization And Antioxidant Activities Of Some Chalcone Derivatives Containing 2-Chlorothiophene Moiety - Ng, Weng Zhun (2021)
A total of twelve heterocyclic chalcone compounds (1a-1l) containing 2-chlorothiophene moieties were synthesized using Claisen Schmidt Condensation process and were crystallized by slow evaporation methods. The postulate structure of these heterocyclic chalcone compounds were elucidated by FT-IR and NMR spectral analyses, followed by single crystal X-ray diffraction technique. Besides, the antioxidant potential of all compounds was evaluated using four different types of antioxidant assay which include 2, 2-diphenyl-1-picrylhydrazyl (DPPH), ferrous ion chelating (FIC), nitric oxide (NO) and Hydrogen Peroxide (H2O2) radical scavenging assay. Nine compounds are crystallized in monoclinic space group with four compounds in P21/c, three compounds in P21/n and two compounds in Cc and Pc. Another, two compounds are crystallized in triclinic space group